Long-term outcomes of stroke unit care in older stroke patients: a retrospective cohort study. (3rd September 2022) - Geraedts, Max; Ebbeler, Dijana; Timmesfeld, Nina; Kaps, Manfred; Berger, Klaus; Misselwitz, Björn; Günster, Christian; Dröge, Patrik; Schneider, Michael
Abstract: Background: older patients are less frequently treated in stroke units (SUs). Clinicians do not seem convinced that older patients benefit from specialised treatment in SU similarly to younger patients. Objective: our study aimed to compare older patients' long-term outcomes with and without SU treatment. Methods: this study used routinely collected health data of 232, 447 patients admitted to hospitals in Germany between 2007 and 2017 who were diagnosed with ischaemic stroke (ICD 10 I63). The sample included 29, 885 patients aged ≥90 years. The outcomes analysed were 10-, 30- and 90-day, and 1-, 3- and 5-year mortality and the combinations of death or recurrence, inpatient treatment and increase in long-term care needs. Bivariate chi-square tests and multivariable logistic regression analyses were used, adjusting for the covariates age, sex, co-morbidity, long-term care needs before stroke and socioeconomic status of the patients' region of origin. Results: between 2007 and 2017, 57.1% of patients aged <90 years and 49.6% of those aged ≥90 years were treated in a SU. The 1-year mortality rate of ≥90-year-olds was 56.9 and 61.9% with and without SU treatment, respectively. The multivariable-adjusted risk of death in ≥90-year-olds with SU treatment was odds ratio (OR) = 0.67 (95% confidence interval [CI] = 0.62–0.73) 10 days after the initial event and OR = 0.76 (95% CI = 0.71–0.82) 3 years after stroke. Conclusions: even very old patients with stroke benefit from SU treatment in the short and long term. Therefore, SU treatment should be the norm even in older patients.